Optimisation of regeneration unit to achieve zero discharge in a paper mill - Foo, Dominic Chwan Yee; Abdul Manan, Zainuddin (2005)
The advent of water pinch analysis as a tool for the design of optimal water recovery network has been one of the most significant advances in the area of water conservation over the last decade. Water pinch analysis is a systematic technique for implementing strategies to maximise water reuse and recycling through integration of water-using activities or processes. In this paper, possibility of achieving complete elimination of wastewater, i.e. zero discharge is assessed through the use of water regeneration units. Water regeneration has been widely accepted as an effective mean to further reduce water targets in water pinch analysis. Water regeneration involves the partial or total upgrading of water purity using any purification techniques. The regenerated water can either be reused in other water-using processes or recycled to the same process to further reduce water consumption and wastewater generation. A case study on a water-intensive paper mill process is used to illustrate how the water network can be optimised to achieve zero discharge. The targeting technique of water cascade analysis is used to locate the various network targets prior to the development of detailed network design. A solution with the minimum capital and annual operating costs was obtained.